Sea Breeze Sensitivity to Coastal Upwelling and Synoptic Flow Using Lagrangian Methods. Issue 17 (12th September 2018) - Seroka, Greg; Fredj, Erick; Kohut, Josh; Dunk, Rich; Miles, Travis; Glenn, Scott
Abstract: Sea breezes occur nearly daily in the U.S. Mid‐Atlantic summer during high electricity demand periods, and thus have important implications for the burgeoning U.S. offshore wind energy industry. The sea breeze's offshore component is poorly understood and ill defined relative to its onshore counterpart. Here a new Lagrangian method not yet readily used to study the sea breeze, relative dispersion, was validated and applied to a validated Weather Research and Forecasting model in the U.S. Mid‐Atlantic. This Lagrangian method is used to characterize the onshore convergent and offshore divergent sea breeze extents and intensities, and test their sensitivities to both atmospheric synoptic flow and oceanic coastal upwelling, another common summer season regional phenomenon. It was found that offshore‐directed synoptic flow impacted the sea breeze onshore extent more than offshore extent, and that coastal upwelling did not significantly impact sea breeze onshore or offshore extent for these carefully selected case studies. Upwelling, however, produced an earlier sea breeze onset (~5 hr), and a shallower, sharper, and more intense offshore/onshore sea breeze during strong offshore synoptic flow, consistent with past studies. The offshore side of the sea breeze cell—with stronger intensity during upwelling—crossed the New Jersey Wind Energy Area at ~1900 UTC, regardless of synoptic wind or upwelling conditions. Results overall are consistent with dynamic linear sea breeze theory. Uncertain projected trends in coastal upwelling/sea breezes in a warming world highlight the importance of continued study of coastal air‐sea interactions for improved offshore wind energy assessment and prediction. Plain Language Summary: Sea breezes are important for the emerging U.S. offshore wind energy industry, because they occur frequently during peak energy demand periods (summer afternoons) across many of the nation's coastlines designated for offshore wind energy. However, the offshore component of the sea breeze—where offshore wind turbines operate—is poorly understood. Here a Lagrangian analysis technique called relative dispersion is newly applied to a numerical weather prediction model in the U.S. Mid‐Atlantic. The new technique enables clearer characterization of the offshore sea breeze component. It was found that winds against the sea breeze prevented the sea breeze from penetrating inland, whereas those same winds largely did not affect the offshore extent of the sea breeze. When coastal upwelling occurred—resulting in very cold waters at the beach, the sea breeze began ~5 hr earlier and was stronger. Regardless of the condition tested, the offshore extent of the sea breeze crossed the New Jersey Wind Energy Area at ~1900 UTC. The results here are consistent with past studies and sea breeze theory. The new application of the technique should be a useful tool for further characterization and prediction of the sea breeze offshore, which will be critical for offshore wind energy applications. Key Points: Lagrangian method applied to weather model reveals synoptic flow impacts sea breeze onshore extent more than offshore in U.S. Mid‐Atlantic Upwelling did not greatly impact sea breeze onshore/offshore extent, but produced earlier, shallower, sharper, and stronger sea breeze Results agree with sea breeze theory, proving utility of Lagrangian methods for sea breeze prediction, offshore wind resource assessment